Visual artificial intelligence as a co-creative partner in foresight scenario creation - Grison, Priscila (2025)
In Strategic Foresight, imagining future scenarios is essential for envisioning diverse futures. However, cognitive barriers and hegemonic worldviews often limit the ability to project alternative scenarios. Visual AI tools, especially those that generate images, present new opportunities to overcome these limitations in scenario creation. Despite this potential, little research has explored how these tools can systematically support the scenario-creation process while addressing the biases embedded in AI tools themselves. This exploratory study aimed to develop and test a method that incorporates Visual AI as a co-creation tool, combining cognitive science insights with foresight practices in a human-AI hybrid model. Using Design Science Research as the research approach, the study developed a conceptual framework and method, which were further developed and evaluated through Action Research. In this context, participants utilized AI-generated images to represent scenarios. Results indicate that Visual AI helps participants overcome cognitive barriers, inspiring new ideas, contributing with novel concepts, and enhancing collaborative imagination, resulting in a higher quantity and variety of concepts and expanding the space of possibility. This research contributes a structured approach for integrating AI-generated visuals in Foresight, along with recommendations for facilitation techniques in human-AI hybrid workshops.